Potensi Biomassa dan Karbon di Atas Permukaan Tanah pada Vegetasi Mangrove Rewata’a, Kabupaten Majene - Ritabulan; Suparjo Razasli Carong; Yusna (Pangale Journal of Forestry and Environment, 2023)
This research aims to calculate the potential for biomass and aboveground carbon in mangrove vegetation in the Rewata'a mangrove ecosystem area, Majene Regency. Data collection was carried out by taking samples from 20 plots measuring 20x20 meters. Data analysis uses allometric equations for biomass estimation and an approach with 0.47 biomass as carbon in mangrove trees (BSN, 2011). The analysis results show that the potential for biomass and carbon stored above ground in mangrove vegetation in the Rewata'a mangrove area respectively is 173.75 tonnes/ha and 81.66 tonnesC/ha. Key words: biomass, carbon stock, mangrove, climate change, vegetation